Different Treatment Bagi Eksil Korban Peristiwa 1965 di Eropa - Yohanes Victor Baro Bitan Lamatokan; Robertus Wijanarko (Jurnal Hukum dan Sosial Politik, 2024)
This article examines the differential treatment of so-called exiles, people who were sent abroad either to study or to work. During the events of 1965-1966, their passports were revoked. They lived by moving from one country to another in search of a "home" that would accommodate them. The exiles traveled to various countries, including the Netherlands, France, Germany, Sweden and the United States. During this time, they experienced various difficulties, economically, socially and psychologically. Economically, they struggled to find work, socially, they experienced discrimination and psychologically, they were deeply traumatized and haunted by fear. The story of the suffering they experience contradicts the rights they should get as Indonesian citizens when they are abroad. The theoretical framework used is John Locke's liberalism, which clearly supports the equal rights of every citizen to ultimately create harmony between them. It is this equality of rights that this study aims to investigate. This research uses a qualitative approach that draws on literature, internet pages and interview narratives. As a result of the research, one of the exiles interviewed admitted that he was still proud to be an Indonesian citizen even though he did not get the same treatment as an Indonesian citizen.